2013
DOI: 10.5894/rgci416
|View full text |Cite
|
Sign up to set email alerts
|

Percepção ambiental dos moradores da cidade de São Vicente sobre os resíduos sólidos na Praia do Gonzaguinha, SP, Brasil

Abstract: A poluição de praias por resíduos sólidos é um problema bem registrado mundialmente. Entre os fatores que influenciam para essa poluição está o número de usuários do ambiente. Em Lucena-PB é durante o período de Carnaval que se registra o maior numero de usuários em suas praias, chegando a triplicar sua população (15 mil habitantes). Dessa forma este estudo teve como objetivo testar a hipótese de que as áreas onde estavam sendo realizados os eventos de Carnaval apresentam maior quantidade de resíduos. Para tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
4
0
11
Order By: Relevance
“…The main source of income for Cananeia and other municipalities in the region are fishing and tourism and those depend on the quality of the fisheries and of the natural environment (MENDONÇA, 2007). Ferraro-Junior (2007) considers it essential that there should be some possibility of working with themes that are related to the participants' own contexts so that they will be able to interact with the themes. According to Freire (2005), teaching by means of 'generating themes' transcends the mere basic understanding of the words because the topics have a place in everyday life.…”
Section: Contextualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main source of income for Cananeia and other municipalities in the region are fishing and tourism and those depend on the quality of the fisheries and of the natural environment (MENDONÇA, 2007). Ferraro-Junior (2007) considers it essential that there should be some possibility of working with themes that are related to the participants' own contexts so that they will be able to interact with the themes. According to Freire (2005), teaching by means of 'generating themes' transcends the mere basic understanding of the words because the topics have a place in everyday life.…”
Section: Contextualizationmentioning
confidence: 99%
“…As mentioned above, some authors underscore the problem of the failure to acknowledge the question of marine debris as a global environmental problem that calls for far greater efforts and programs and public policies duly adapted to each context. Fernandes and Sansolo (2013) investigated the environmental perceptions of residents of a beach in the state of Sao Paulo state in regard to marine debris and showed that the participants in their research acknowledged that part of the debris stemmed from the beach-users themselves. At the end of the set of meetings all the participants agreed that marine debris is indeed an important, complex of environmental problem awaiting solution because the latter depends on various different segments of society.…”
Section: Iv) Perceptions Of and Responsibility For The Impactsmentioning
confidence: 99%
“…A análise dos dados da percepção dos usuá rios é feita utilizandose métodos da estatística des critiva, os quais permitem analisar a distribuição de frequência absoluta e relativa e identificar as catego rias nominais e ordinais que se destacam por apre sentar maior frequência. As técnicas empregadas no estudo de per cepção ambiental consistem da combinação de três métodos básicos: observar, escutar e fazer perguntas (Fernandes & Sansolo, 2013), sendo esta pesquisa foi realizada em duas etapas: (1) levantamento preli minar de dados; e (2) aplicação de questionário.…”
Section: Metodologia De Trabalhounclassified
“…O estudo da percepção ambiental é de funda mental importância para a compreensão das inter relações entre o homem e o meio, valores e expecta tivas da sociedade na busca por qualidade da paisagem e do meio ambiente (Palma, 2005;Marin, 2008;Souza, 2009;Fernandes & Sansolo, 2013). Nesta área, destacamse os trabalhos de Morgan et al (1993), Priskin (2003), Roca et al (2009) e Bittencourt et al (2011), que servem de referência para este estudo.…”
Section: Introductionunclassified
“…Neste sentido, depende da interação entre o indivíduo e o ambiente em que ele está inserido (FERNANDES; SANSOLO, 2013). O visitante valoriza o espaço pela beleza natural, importância ecológica e social, porém, não tem laços de afetividade.…”
Section: Introductionunclassified